CHRISTIAN VALUES IN EDUCATION AS A CONTRIBUTING FACTOR TO TOLERANCE WITHIN THE INDONESIAN CHINESE COMMUNITY - Evans Winata; Ellya Nora Manurung; David Samuel; Damai Wijaya; Suranto (CV Naskah Aceh, 2026)
This article observes the dynamics of coexistence within the Indonesian Chinese community, a community that is itself internally diverse in terms of religion. Within a single community, and even within a single family, one may find members who practice Buddhism, Catholicism, Protestant Christianity, and in smaller numbers, Islam. Despite this diversity, the community generally demonstrates a relatively high degree of tolerance in daily life, with friction that tends to be minor and limited to matters related to religious ritual. This article seeks to trace one of the factors that contributes to this pattern of tolerance, particularly from the perspective of Christian values in religious education. The argument proposed is that the biblical command to honor one's parents, as contained in the Fifth Commandment of the Ten Commandments, practically functions as a moral restraint for young Christians when facing religious differences with parents who still practice Buddhism. This tends to encourage a persuasive and patient approach rather than a confrontational one, and in turn helps preserve harmony within families and the broader community. The article also reflects on the pastoral implications of this pattern, including the fairly common phenomenon in which some parents come to express faith in Christ near the end of their lives.